Location of urban micro‐consolidation centers to reduce the social cost of last‐mile deliveries of cargo: A heuristic approach. Issue 3 (9th August 2021) - Arrieta‐Prieto, Mario; Ismael, Abdelrahman; Rivera‐Gonzalez, Carlos; Mitchell, John E.
Abstract: Urban deliveries of goods have become a rising challenge due to the increase of online shopping in addition to the traditional business‐to‐business (B2B) dynamics. To maintain a satisfactory level of service, carriers must conduct delivery operations under restrictive environments, creating undesirable externalities such as congestion and pollution. Urban micro‐consolidation centers (UMCs) are defined as on‐street or off‐street spaces where all the deliveries within a certain radius are dropped and reconsolidated to be delivered by more sustainable last‐leg modes. Their main purpose is to mitigate such negative externalities. This work formulates the last‐mile delivery problem assisted by UMCs as a mixed‐integer quadratically‐constrained program and develops a greedy heuristic solution, inspired by the decomposition algorithms for large‐scale optimization. The simulation results and a case study in Manhattan, New York show how the heuristic provides reasonable results with respect to the exact solution while also shedding light on how its solution can be utilized for freight‐efficient urban design and policy planning.